Exploring the Role of State-Owned Enterprise Branding in Realizing Digital Sovereignty and Global Competitiveness: A Qualitative Approach through the Integrated Experience Framework within the AX–BX–CX–DX Ecosystem - Muhammad Awaluddin (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This study explores the strategic role of state-owned enterprise (SOE) branding in realizing digital sovereignty and strengthening global competitiveness through the AX–BX–CX–DX Integrated Experience Framework. It aims to conceptualize how audience perception (AX), brand identity (BX), customer loyalty (CX), and digital governance (DX) interact to form a sovereign and adaptive brand ecosystem. Employing a qualitative–descriptive design, the research integrates conceptual analysis with empirical case exploration of leading Indonesian SOEs such as Telkom Indonesia, Pertamina, and BRI. Data were collected through literature synthesis, document analysis, and social listening to examine public sentiment and digital narratives. The inductive–deductive analytical approach ensured coherence and interpretive depth. Findings reveal that the synergy among AX–BX–CX–DX dimensions fosters a data-driven, human-centered brand governance system that enhances national digital legitimacy. Practically, this study highlights the need for AI-driven branding, digital talent empowerment, and ESG-oriented brand storytelling to strengthen SOEs’ competitiveness and trust capital. Theoretically, it contributes to the intersection of nation branding, experience economy, and corporate diplomacy, positioning SOEs as sovereign digital ambassadors of national identity.